International Finance - Sercu, Piet (Princeton, 2001)
International Finance presents the corporate uses of international financial markets to upper undergraduate and graduate students of business finance and financial economics. Combining practical knowledge, up-to-date theories, and real-world applications, this textbook explores issues of valuation, funding, and risk management. International Finance shows how theoretical applications can be brought into managerial practice. The text includes an extensive introduction followed by three main sections: currency markets; exchange risk, exposure, and risk management; and long-term international funding and direct investment. Each section begins with a short case study, and each of the sections' chapters concludes with a CFO summary, examining how a hypothetical chief financial officer might apply topics to a managerial setting. The book also contains end-of-chapter questions to help students grasp the material presented. Focusing on international markets and multinational corporate finance, International Finance is the go-to resource for students seeking a complete understanding of the field. Rigorous focus on international financial markets and corporate finance concepts An up-to-date and practice-oriented approach Strong real-world examples and applications Comprehensive look at valuation, funding, and risk management Introductory case studies and "CFO summaries," and end-of-chapter quiz questions Solutions to the quiz questions are available online.